The Influence Of Training And Industrial Relations On Work Productivity And Its Impact On Employee Performance - Aip Zaenal Mutaqin; Zakie Shiddieqi; Hasan Firdaus (CV. Astina Mandiri, 2024)
Work productivity is a vital determinant of organizational success, encompassing both the quality and quantity of output. At PT. XYZ Garut, a steel manufacturing company, enhancing employee productivity is achieved through education and training (Diklat) programs aimed at improving skills and competencies. Additionally, the company prioritizes harmonious industrial relations to foster a conducive working environment. This study investigates the influence of training and industrial relations on work productivity and their subsequent impact on employee performance. Using associative research with saturated sampling involving 98 employees, data analysis revealed that training contributes 37.4% and industrial relations 42.0% to work productivity. Combined, these factors account for 50.6% of productivity improvements. Moreover, work productivity significantly influences employee performance, contributing 32.1%. Statistical tests confirmed these relationships, with positive regression coefficients indicating that effective training and harmonious industrial relations directly enhance productivity and performance. The findings emphasize the importance of targeted training programs and strong industrial relations policies in achieving organizational goals. Recommendations include systematic training, motivation enhancement, and recognition initiatives to sustain high employee morale and collaboration.